2020
DOI: 10.1097/ede.0000000000001196
|View full text |Cite
|
Sign up to set email alerts
|

Weight-lowering Effects of Glucagon-like Peptide-1 Receptor Agonists and Detection of Breast Cancer Among Obese Women with Diabetes

Abstract: Weight-lowering effects of glucagon-like peptide-1 receptor agonists and detection of breast cancer among obese women with diabetes. Epidemiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…49 Moreover, the weight-lowering effects of GLP-1RAs may increase BC incidence by easing the process of finding already present breast lumps, leading to early diagnosis of cancer. 19,28 Furthermore, postmenopausal women who lose weight over the long term have a lower risk of BC development. 50 The current study investigated the impact of incretinbased medication administration on BC incidence in women with T2DM using a meta-analysis of cohort studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…49 Moreover, the weight-lowering effects of GLP-1RAs may increase BC incidence by easing the process of finding already present breast lumps, leading to early diagnosis of cancer. 19,28 Furthermore, postmenopausal women who lose weight over the long term have a lower risk of BC development. 50 The current study investigated the impact of incretinbased medication administration on BC incidence in women with T2DM using a meta-analysis of cohort studies.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, four cohort studies were included: two studies found no association between incretins and BC incidence, one indicated protective roles against BC, and one showed an increase in BC detection with incretin-based therapies. 22,23,28,29 Due to the discordant results regarding the connection between incretins and BC, it was necessary to conduct a systematic review and meta-analysis of studies with longer-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Acute pancreatitis was rst reported in case reports in 2006 [11,12]. Additionally, the possible long-term effects of GLP-1RAs on pancreatic cancer were investigated [13,14]. A pharmacovigilance analysis based on the US Food and Drug Administration (FDA) adverse event reporting system suggested an increased risk of pancreatitis with GLP1RA when only exenatide was approved in the US [15].…”
Section: Introductionmentioning
confidence: 99%